Clinical profile of cases of dysphagia presenting in ENT department: a study from rural tertiary care center - Datta, Ginni; Gupta, Manish; Rao, Naiya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Swallowing is a complex motor reflex requiring coordination among the neurologic system and muscles of the oropharynx and oesophagus. Disorders both benign and malignant may interfere with the process and cause dysphagia. We hereby undertake a study in a rural tertiary care centre to study the clinical profile of cases of dysphagia and to find the relative incidence of various etiologies of dysphagia. Methods: A prospective study was conducted upon both out and indoor patients coming to Department of Otorhinolaryngology from January 2016 to January 2017 with predominant symptom of difficulty in swallowing for both solids, liquids or either. Detailed history & examination was done. Further endoscopy, barium swallow, fine needle aspiration cytology (FNAC) & biopsies were done as required. A total of 140 cases were taken into consideration. Results: The mean age was 52.5 years with 60% patients males and 40% females. The commonest etiology of dysphagia was Gastroesophageal reflux disease (GERD) occupying 28.57%of cases. Among them 65% werefemales majority in the age group of 45-55 years. The 2nd common cause of dysphagia was growth pharynx 18.5% of cases. Among them 19 cases were diagnosed as growth oropharynx and 7 cases as growth supraglottis extending to hypopharynx. 88.46% were males and all were smokers. The 3rd common etiology of dysphagia was obstructive oesophageal causes which included oesophageal malignancies, oesophageal webs, strictures and diverticula in the frequency of 16%, 3%, 3% and 6% respectively. Oesophageal malignancies were mainly adenocarcinoma, all males who were chronic smokers. Conclusions: Dysphagia is a commonly encountered clinical problem & limited studies exist regarding the prevalence of dysphagia etiologies. It is an alarm symptom, malignancy should be ruled out, and warrants early intervention.